2010
DOI: 10.1111/j.1469-0691.2009.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Crimean-Congo haemorrhagic fever

Abstract: Crimean-Congo Hemorrhagic fever (CCHF) is a potentially fatal viral infection with reported case fatality rates of 5-30%. Humans become infected through tick bites, by contact with a patient with CCHF during the acute phase of infection, or by contact with blood or tissues from viraemic livestock. In this first report in the literature, we present the characteristics of three pregnant women with CCHF infection and the outcome of their babies. Transmission of the CCHF infection could be either intrauterine or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 9 publications
1
25
0
3
Order By: Relevance
“…KKKA'da annenin yaşamının kurtarılması için fetusun tahliyesi gerekebilir; yenidoğanlarda fatalite oranı yüksektir (45). Ribavirin kullanımı gebelikte kontrindikedir (FDA gebelik kategorisi X); ama annenin yaşamının kurtarılması icin gerekli olabilir.…”
Section: Gebelikte Ribavirin Kullanımıunclassified
“…KKKA'da annenin yaşamının kurtarılması için fetusun tahliyesi gerekebilir; yenidoğanlarda fatalite oranı yüksektir (45). Ribavirin kullanımı gebelikte kontrindikedir (FDA gebelik kategorisi X); ama annenin yaşamının kurtarılması icin gerekli olabilir.…”
Section: Gebelikte Ribavirin Kullanımıunclassified
“…CCHF should be differentiated from HELLP syndrome (hemolytic anemia, elevated liver enzymes, low platelet count) encountered during the pregnancy. 8,9 Tezeret et al,5 in their study on 31 pediatric patients diagnosed with CCHF, reported that all patients recovered from the disease. In addition, laboratory signs and clinical progressions of children were better than those of adults, and the disease progressed more mildly during childhood; however, some pediatric mortal cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal transmission of the disease from mother to the fetus was shown. 7 In the study conducted on pregnant CCHF patients by Ergonul et al 8, three pregnant women were followed up, and the virus was detected in the fetus of one patient by using RT-PCR and ELISA. They also reported that one of three patients died with the fetus, whereas other pregnant patients recovered while losing their fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of three pregnant women with CCHF in Turkey, both the mother and fetus died in one case, and the babies of the two surviving patients died after birth. The authors emphasized that CCHF can cause miscarriage, neonatal complications, and death in pregnant patients, and concluded that outcomes were related to the gestation period (trimester) and the disease severity [74] . In a case report of a patient infected with CCHF in week 30 of pregnancy, the baby was born at 37 weeks completely healthy with no signs or symptoms related to the disease [75] .…”
Section: Prognostic Factors Fatality and Discharge Criteriamentioning
confidence: 99%